The organizer: towards professionalism and safety in undergraduates jewellery fabrication process / Mohd Faiz Jalaludin and Mohd Hakim Mohd Sharif - Jalaludin, Mohd Faiz; Mohd Sharif, Mohd Hakim (Universiti Teknologi MARA, Perak, 2020)
Hand tools arrangement while doing any fabrication process is a very important thing that is always neglected by many people not just by professional fabricators but also by undergraduates. Any dangerous tools like sharp, flammable and corrosive tools must be arranged in a safe location while doing any fabrication process, especially jewellery fabrication. The objective of this design idea is to initiate a safer working environment for undergraduate students, to make the jewellery making process become more easier with effective arrangement of tools while doing any fabrication process and to introduce jewellery tools organizer as a part of safety features in jewellery making process. This design will be focused on how to arrange jewellery hand tools based on personal experience, observation and references on current issues. Other than the usability elements, the design will also consider the affordable price for undergraduate students and the design must be portable because undergraduate students are not professional practitioners that usually have their own working station. Based on that design, students' temporary working station at their university or any education center will become more organized and safer. Organized and safe working environment will cultivate professional working experiences and will affect their result of designing and fabricating jewellery.